2010
DOI: 10.1093/humrep/deq312
|View full text |Cite
|
Sign up to set email alerts
|

Dioxins in ascites and serum of women with endometriosis: a pilot study

Abstract: This is the first report suggesting that higher concentrations of dioxins (PCDDs and PCDFs) in peritoneal fluid are linked to endometriosis. More detail and epidemiological research is warranted to further explore this link.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 37 publications
0
15
1
Order By: Relevance
“…Indeed, growing evidence suggests that the peritoneal fluid plays a critical role in the implantation and progression of endometriosis (revised by Koninckx et al 1998). Peritoneal fluid contains detectable levels of dioxin or dioxin-like compounds such as 2,3,7,8-tetrachlorodibenzo-pdioxin (TCDD) depending on individual exposure (Cai et al 2011) and it has been recently shown that the adipose tissue from the omentum in women with endometriosis contains a greater amount of dioxin-like compounds when compared with age and body mass index-matched controls (Martinez-Zamora et al 2015). One can speculate that such compounds are involved in endometriosis as they can transcriptionally induce CYP1B1 and CYP1A1 in explant cultures of human endometrial or stromal cells (Bofinger et al 2001), mostly by their interaction with nuclear receptors, as the resulting complexes bind to the regulatory region of the gene and modulate CYP expression (Waxman 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, growing evidence suggests that the peritoneal fluid plays a critical role in the implantation and progression of endometriosis (revised by Koninckx et al 1998). Peritoneal fluid contains detectable levels of dioxin or dioxin-like compounds such as 2,3,7,8-tetrachlorodibenzo-pdioxin (TCDD) depending on individual exposure (Cai et al 2011) and it has been recently shown that the adipose tissue from the omentum in women with endometriosis contains a greater amount of dioxin-like compounds when compared with age and body mass index-matched controls (Martinez-Zamora et al 2015). One can speculate that such compounds are involved in endometriosis as they can transcriptionally induce CYP1B1 and CYP1A1 in explant cultures of human endometrial or stromal cells (Bofinger et al 2001), mostly by their interaction with nuclear receptors, as the resulting complexes bind to the regulatory region of the gene and modulate CYP expression (Waxman 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Dioxin exposure (47,324) and exposure to the a phthalate BzBP metabolite and its metabolites MBz, P and the DEP metabolite MEP may be associated with increased risk of endometriosis (63), although BPA exposure was not linked in an epidemiological study of women with endometriosis (350). One large cross-sectional study from the United States demonstrated an association of MBP with an increased risk of endometriosis (366), and another did not confirm the associations of phthalate exposure with endometriosis and demonstrated that MEHP had an inverse association with the presence of endometriosis (351).…”
Section: Endocrine Disrupting Chemicalsmentioning
confidence: 99%
“…58 The increased incidence of endometriosis being noted in areas of high xenoestrogen exposure 59 raises the question whether the genetic defect developed first in the mother because of her prior exposure, or was caused by the de novo exposure of the offspring to xenoestrogen in utero. In either case, the link of endometriosis and xenoestrogens such as dioxin, 60 at least in select cases, has been established.…”
Section: Geneticsmentioning
confidence: 99%